If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(m-10)+1=2(m-8)
We move all terms to the left:
3(m-10)+1-(2(m-8))=0
We multiply parentheses
3m-(2(m-8))-30+1=0
We calculate terms in parentheses: -(2(m-8)), so:We add all the numbers together, and all the variables
2(m-8)
We multiply parentheses
2m-16
Back to the equation:
-(2m-16)
3m-(2m-16)-29=0
We get rid of parentheses
3m-2m+16-29=0
We add all the numbers together, and all the variables
m-13=0
We move all terms containing m to the left, all other terms to the right
m=13
| 5(a+a+a=) | | X.2(4x-3)-8=4+2x | | 8t=7t+7 | | 96+4x+4x+(5x+2)+(5x+8)=540 | | -4.3g=25 | | x-3/x=3/12 | | -3z-1=+2-1 | | 12x+5=15x-25 | | -4+-20d=4 | | 4(x-2)-(1/5)(20x+5)=32 | | 4(5x+2)=20x-7 | | 5(x+9)=27 | | 4=1x+46 | | -5(4n+12)+2n=12(n-5) | | 3.4−0.2x=2.9+1.8x | | 6(x-2)+5=-x | | 4(x–3)+8=92 | | (2x+2)+(2x+2)+(2x+2)+(2x+2)=0 | | 11+3x-7=6x+5=3x | | -6+9p=8p | | 12−6(8u−5)=−54 | | 2-5(x+10)=6+3x | | 4(x+3.29)=11.16 | | -9p=9-8p | | 2(x+2)=110 | | -7i(-8i)=0 | | 10(-2x-3)=6(-2x-9) | | 7(4w+2)/3=-8 | | 4x-24=3x=21 | | 50+3.7=50-1.9x | | 84-12y=180 | | –6+9p=8p |